Power to decide on development applications under the National Land Code 1965: the position in Selangor - Syed Abdul Kader, Sharifah Zubaidah (International Islamic University Malaysia, 2004)
Thia article addresses the general issue of over concentration of powers in land decision-making on the executive in the majority of states in Malaysia. The writer focuses on one of the mechanisms used to achieve this; namely through the administrative technique of delegation of powers. Statutes conferring administrative powers sometimes confer on the administrative authority the power to delegate such powers to other officers. This article examines the nature of land development applications and the type of powers delegated in the state of Selangor with regard to land matters. Based on the premise that where there is already a provision for delegation of powers under the National Land Code, 1965, powers under this Code should not be delegated to the executive under a general delegation of power statute, the writer accordingly proposes that the power of the State Authority to delegate powers under the Code be restricted.